Intraoperative Characterization of Pancreatic Tumors Using Contrast‐Enhanced Ultrasound and Shear Wave Elastography for Optimization of Surgical Strategies. (30th October 2020) - Platz Batista da Silva, Natascha; Engeßer, Maria; Hackl, Christina; Brunner, Stefan; Hornung, Matthias; Schlitt, Hans J.; Evert, Katja; Stroszczynski, Christian; Jung, Ernst Michael
Abstract : Objectives: To evaluate intraoperative contrast‐enhanced ultrasound (IoCEUS) and intraoperative shear wave elastography (IoSWE) for characterization of focal pancreatic lesions (FPLs) in correlation with postoperative histologic results. Thereby, the impact of intraoperative ultrasound (US) on pancreas surgery was evaluated. Methods: Intraoperative CEUS and SWE data from 54 patients, who underwent pancreas surgery between 2017 and 2019, were analyzed retrospectively. Ultrasound examinations were performed with multifrequency linear/T‐shaped transducers (3–9 MHz) on a high‐end US device (LOGIQ E9; GE Healthcare, Chicago, IL). To analyze FPL stiffness by SWE, regions of interest were placed to measure the shear wave speed (meters per second) and stiffness (kilopascals). After intravenous bolus injections of 2.4 to 10 mL of sulfur hexafluoride microbubbles, a dynamic analysis of FPL microvascularization from arterial to late phases was performed using IoCEUS considering hypoenhancement/irregular vascularization of macrocystic/small solid FPL malignancy criteria. Ultrasound findings were correlated with postoperative histologic results. The impact of intraoperative US on surgery was documented in each case. Results: Of 54 FPLs, IoCEUS could correctly characterize 39 of 39 malignant and 6 of 15 benign FPLs; IoSWE 29 of 39 as malignant and 7 of 15 as benign. Intraoperative CEUS's sensitivity was 100%; specificity, 40%; accuracy, 83.3%; positive predictive value, 81.3%; and negative predictive value, 100% ( P  < .05). Applying cutoff values of 3 m/s and 28.7 kPa, SWE's sensitivity was 74.4%; specificity, 46.7%; accuracy, 66.7%; positive predictive value; 78.4%; and negative predictive value, 41.2% for cancer detection ( P  < .05). The combined use of both techniques showed an accuracy rate of 76%, sensitivity of 74.4%, and specificity of 33.3%. In 29.6%, US results had an immediate impact on surgery. Conclusions: Intraoperative SWE and CEUS are highly valuable techniques for intraoperative characterization of FPLs. Although IoCEUS proved to be superior to IoSWE, the combined use can be helpful in particular cases.